Trends in Biopsy-Based Diagnosis of Kidney Disease: A Population Study. Issue 1 (September 2018) - Cunningham, Amanda; Benediktsson, Hallgrimur; Muruve, Daniel A.; Hildebrand, Ainslie M.; Ravani, Pietro
Background: Kidney biopsy is considered the gold standard for diagnosis of renal disease. It is increasingly performed in cases of diagnostic uncertainty, including in patients with coexistent diabetes and hypertension, for which a presumptive clinical diagnosis can be made. Little is known about the incidence and distribution of biopsy-proven kidney diseases. Changes in the distribution of biopsy diagnoses over time may have significant implications for resource allocation and future research. Objective: We studied the relative frequency of kidney diseases in Southern Alberta over the past 30 years, to determine whether the population-standardized annual biopsy rate and incidence of selected diagnostic categories have changed. We hypothesized an increasing incidence of renal biopsies and a growing proportion of nonglomerular diseases (eg, tubulointerstitial disorders) likely due to evolving indications for biopsy. Given the rise in obesity, diabetes, and aging population with chronic kidney disease (CKD), we anticipated a rise in nephroangiosclerosis and diabetic nephropathy over time. Design: Retrospective population-based cohort study using the Biobank for the Molecular Classification of Kidney Disease (BMCKD). Setting: Southern Alberta, Canada. Patients: All patients who underwent renal biopsy between 1985 and 2015 in our database. Measurements: We used descriptive and quantitative analysis to characterize demographics and biopsy-based diagnoses. Methods: We conducted a retrospective population-based cohort study to analyze all consecutive patients who underwent at least one kidney biopsy over a 30-year period in Southern Alberta (1985-2015). We considered the first adequate biopsy. We described the annual standardized incidence of biopsy-proven kidney diseases over time and summarized associated patient characteristics. We assumed a Poisson distribution for biopsy counts and used provincial demographic information to standardize rates. Results: During the study period, 6434 people (58% male; mean age: 47.9 years) underwent a kidney biopsy. The population-standardized annual biopsy rate increased from 10.8 biopsies per 100 000 person-years in the first 5 years of the study (1985-1989) to 18.2 biopsies per 100 000 person-years in the last 5 years (2010-2014). The mean age at the time of biopsy increased from 42.5 years (1985-1989) to 51.4 years (2010-2014). Glomerular diseases remained the most prevalent histopathological group, with a growing representation of diabetic kidney disease from 3.69% to 16.18%, and a relative decrease in the proportion of other glomerular diseases from 72.32% to 62.92% of glomerular diagnoses. Tubulointerstitial diseases increased from 5.87% to 7.36% of total diagnoses. Limitations: Classification schemes have changed over time, so recently recognized conditions may have been misclassified in earlier data. There was a changing group of pathologists and nephrologists over this period. Variations in interpretation and application of biopsy indications by physician may influence recorded prevalence of certain diagnoses. We do not yet have complete information on indications or patient outcomes linked to the database. Conclusions: In Southern Alberta, kidney biopsy is being utilized more frequently and in older people. Diabetic nephropathy is increasingly diagnosed, which may reflect either or both changes in the prevalence of causative factors and local biopsy practices.